Exposing behavioral differences in cross-language API mapping relations - Thummalapenta, Suresh (FASE'13: Proceedings of the 16th international conference on Fundamental Approaches to Software Engineering, 2013)
Due to various considerations, software vendors often translate their applications from one programming language to another, either manually or with the support of translation tools. Both these scenarios require translation of many call sites of API elements (i.e., classes, methods, and fields of API libraries). API mapping relations, either acquired by experienced programmers or already incorporated in translation tools, are much valuable in the translation process, since they describe mapping relations between source API elements and their equivalent target API elements. However, in an API mapping relation, a source API element and its target API elements may have behavioral differences, and such differences could lead to defects in the translated code. So far, to the best of our knowledge, there exists no previous study for exposing or understanding such differences. In this paper, we make the first attempt to expose and analyze behavioral differences in cross-language API mapping relations. From our result, we summarize eight findings and their implications that can improve effectiveness of translation tools, and also assist programmers in understanding the differences between mapped API elements of different languages during the translation process. Some exposed behavioral differences can indicate defects in translation tools, and four such new defects were confirmed by the developers of those tools.